Work readiness during COVID-19 among taxibike online drivers in Samarinda, Indonesia - Dina Lusiana Setyowati; Swandari Paramita; Riza Hayati Ifroh; Tanti Asrianti; Efi Fitriani; Wahnadita Rahman (International Journal of Public Health Science (IJPHS), 2021)
COVID-19 caused a pandemic around the world, including in Indonesia. This greatly affected the informal business sector, such as online taxibike drivers. The success of this program to control the spread of COVID-19 is greatly influenced by knowledge, attitudes, and actions in the community. The purpose of this study was to identify behavioral factors during the pandemic. An online survey was conducted with 100 online taxibike drivers using a structured questionnaire and Google Forms. Data were analyzed using the Spearman rank test with CI of 95%. Although most online taxibike drivers have sufficient knowledge about COVID-19, some drivers had important misconceptions about COVID-19, namely that COVID-19 is not contagious, weak immune resistance may cause them to contract COVID-19, and it is highly unlikely that they will contract COVID-19 when leaving the house without wearing a mask, and believing that handwashing with soap and using hand sanitizer will not prevent COVID-19. To address these misconceptions, interventions should be targeted to online taxibike drivers to increase their health education and literacy regarding the urgency of preventing COVID-19. It is also important to consider incorporating both interpersonal approaches and conventional and digital-based groups when encouraging changes in their attitudes and practices towards COVID-19.